STUDI KOMPARATIF EMPAT MADZHAB FIQIH TENTANG HUKUM PUTUS KHITBAH - Faris El Amin (Fakultas Syariah Institut Agama Islam Negeri Palu, 2021)
The phenomenon of breaking the khitbah often occurs. However, there are still many Muslim communities who are still unfamiliar with the implications and the Fiqh when this case occurs. This study aims to describe the different views on the law of breaking the Khitbah and the status of the Hadiah that were submitted during the Khitbah period based on the concept of Fukaha. This study uses a qualitative approach with a literature study design. The data was collected by collecting books which became the reference for the four schools of Fiqh. The results show that: (1) Fukaha have different opinions about the law of breaking the khitbah. The main cause of this difference is due to differences in understanding the texts and principles of covenant fiqh and the absence of a qath'i text in this matter. (2) Fukaha, also have different opinions regarding the status of the items given before the break of the khitbah